A Drosophila melanogaster homolog of the TIS11 family of immediate early genes that can rescue a cdr1 cdc25 mutant strain of fission yeast. - Warbrick, E.; Glover, D.M. (Gene, 1994)
A Drosophila melanogaster (Dm) embryonic cDNA library was screened for genes capable of inhibiting wee1+/mik1+ protein kinase (Pk) function. We expected to identify homologs of the Schizosaccharomyces pombe gene nim1+. This gene encodes a Pk capable of phosphorylating and so inhibiting the wee1+ Pk that in turn inhibits p34cdc2. Dm cDNAs capable of complementing the temperature-sensitive phenotype of a nim1/cdr1 cdc25 double mutant strain were identified and found to fall into two classes. One class encodes the Dm Cdc2 protein. The second cDNA class encodes a novel protein containing a central motif consisting of two tandem repeats of a putative Zn(2+)-finger motif. This region is highly conserved in the TIS11 family of immediate early genes, which in mammalian cells are rapidly and transiently induced in response to 12-O-tetradecanoyl phorbol-13-acetate (TPA) and to mitogens such as epidermal growth factor and fibroblast growth factor.